Light intensity requirements for feeding behaviour by the brown-marbled grouper, Epinephelus fuscoguttatus (Keperluan Keamatan Cahaya untuk Perlakuan Pemakanan Ikan Kerapu Harimau, Epinephelus fuscoguttatus) - Mukai, Yukinori; Lim, Leong Seng; Lu, Kien Chee; Abdul Rashid, Mohamed Kamil; Saad, Shahbudin (Penerbit UKM, 2012)
In this study, we investigated the feeding behavior of the brown-marbled grouper, Epinephelus fuscoguttatus with light intensities ranging over eight orders of magnitude from 0 – 1000 lx to estimate the optimum light intensity for larval rearing. Artemia ingestion rates of E. fuscoguttatus of 36 days and 42 days old larvae were measured in feeding behavior experiments and they were significantly higher with light intensities ≥10 lx compared with feeding rates at ≤ 1 lx. E. fuscoguttatus larvae also exhibited Artemia ingestion rates in the dark or in dim lighting (0 – 1 lx) that were about 20% of the ingestion rates with ≥ 10 lx.